1,1-dichloro-2,2-bis(p-chlorophenyl)ethylene (p,p'-DDE) disrupts the estrogen-androgen balance regulating the growth of hormone-dependent breast cancer cells - Aubé, Michel (BioMed Central, 2008)
INTRODUCTION: Estrogen and androgen signalling pathways exert opposing influences on the proliferation of mammary epithelial and hormone-dependent breast cancer cells. We previously reported that plasma concentrations of 1,1-dichloro-2,2-bis(p-chlorophenyl)ethylene (p,p'-DDE), the main metabolite of the insecticide DDT (1,1,1-trichloro-2,2-bis [p-chlorophenyl]ethane) and a potent androgen antagonist, were associated with tumor aggressiveness in women diagnosed with breast cancer. We sought to examine the biological plausibility of this association by testing the effect of p,p'-DDE on the proliferation of CAMA-1 cells, a human breast cancer cell line that expresses the estrogen receptor alpha (ERα) and the androgen receptor (AR), in the presence of physiological concentrations of estrogens and androgens in the cell culture medium. METHODS: The proliferation of CAMA-1 cells was determined in 96-well plates following a 9-day treatment with p,p'-DDE alone (0.1 to 10 μM) or in combination with 17β-estradiol (E(2)) (100 pM) and dihydrotestosterone (DHT) (100, 500, or 1,000 pM). We also assessed p,p'-DDE-induced modifications in cell cycle entry and the expression of the sex-steroid-dependent genes ESR1, AR, CCND1, and TFF1 (pS2) (mRNA and/or protein). RESULTS: We found that treatment with p,p'-DDE induced a dose-response increase in the proliferation of CAMA-1 cells when cultivated in the presence of physiological concentrations of estrogens and androgens, but not in the absence of sex steroids in the cell culture medium. A similar effect of p,p'-DDE was noted on the proliferation of MCF7-AR1 cells, an estrogen-responsive cell line that was genetically engineered to overexpress the AR. DHT added together with E(2 )to the cell culture medium decreased the recruitment of CAMA-1 cells in the S phase and the expression of ESR1 and CCND1 by comparison with cells treated with E(2 )alone. These androgen-mediated effects were blocked with similar efficacy by p,p'-DDE and the potent antiandrogen hydroxyflutamide. CONCLUSION: Our results suggest that p,p'-DDE could increase breast cancer progression by opposing the androgen signalling pathway that inhibits growth in hormone-responsive breast cancer cells. The potential role of environmental antiandrogens in breast carcinogenesis deserves further investigation.